Contrasting carbon and water flux dynamics in an East African rangeland and cropland - Odongo, Vincent O.; Leitner, Sonja; Arndt, Claudia; Dowling, T. P. F.; Gluecks, I.; Jackowicz-Korczynski, M.; Eklundh, L.; Rinne, J.; Wooster, M.; Merbold, Lutz (International Livestock Research Institute, 2025)
We compare carbon (C) and water dynamics in two East African dryland ecosystems: savanna rangeland and rainfed cropland with minimal tillage over a six-month period. Both ecosystems showed near C neutrality, but with some notable differences. Rangeland exhibited fluctuating C exchange around 0, with distinct C losses and subsequent uptake following episodic rains. Cropland initially acted as a C sink; however, accounting for lateral C export from chickpea harvest shifted its balance to neutral. Cropland also demonstrated higher carbon use efficiency (CUE) and water use efficiency (WUE) during peak growth, linked to agricultural management practices. Our findings emphasize the need to incorporate lateral C fluxes and account for intra-annual variability for accurate C budgeting, while recognizing the co-limitation by water and nitrogen in these drylands. Sustainable land management practices that address complex C-water interactions are critical for enhancing ecosystem resilience and mitigating climate change.